Do Men Whose Wives Work Really Earn Less - Jacobsen, Joyce P.; Rayack, Wendy L. (American Economic Review, 1996)
It is common knowledge among empirical labor economists that household-status variables can enter significantly in wage equations. In particular, a substantial marital wage premium for men has been noted. Recently a series of articles in the management literature has argued that an even larger premium accrues to those married men whose wives do not work for pay (single-earner husbands). Our current study arises in response to perceived deficiencies in the conceptual framework and statistical methods used in these studies.